Effectiveness of Short Message Service Reminder and Counseling of Immunization for Age 18-24 Months - Prihanti, Gita Sekar; Hasna, Alifah; Wijayanti, Cici Cahya; Axpreydasta, Egin Fergian; An Nafi', Eki Yazid; Tikha, Fidya Ainun; Maisuri, Jeliny Bintan; Khusna, Nailil; Ningrum, Sri Setya Wahyu (Jurnal Kesehatan Masyarakat, 2024)
Indonesia now ranks fourth in the world in terms of the largest number of unimmunized children. SMS (Short Message Service) reminders and counseling have been shown to increase outreach, but no research has combined these two interventions. This study aimed to determine the effectiveness of SMS Reminder and Counseling on the knowledge, attitude, and willingness of mothers under five and to find out the factors that influence this willingness. This study used the one-group method, pretest, and posttest design. The samples were 186 children under five (18-24 months) who felt incomplete and mothers who had children under five (control and intervention groups). The Chi-Square test shows significant results during the post-test (p 0.05). The Mc-Nemar test shows the influence of counseling and SMS Reminders on increasing knowledge, attitudes, and willingness (p = 0,000). The logistic regression test shows the factors that affect the advanced immunization of under two years child, that was sufficient knowledge (ρ = 0,000; OR = 13,384; CI = 5,986-29,926). SMS Reminders and counseling affect parents’ knowledge, attitudes, and willingness. Factors affecting parental willingness to continue immunization are adequate knowledge. Collaboration between officials and health agencies, the community, and cellular operators is needed to implement the training of health workers.